Agility and its relationship with of scoring accuracy for young footballers aged (14-16) years - Qassim, Sabah; Kadhim, Yousif (Journal of Physical Education, 2018)
Agility and its relationship with of scoring accuracy for young footballers aged (14-16) yearsAgility is considered one of the most important motor abilities in sports in general and in soccer in particular. These two skills play an integral part in resolving match points. The problem of the study lies in the effect of agility on scoring for youth players. The researcher hypothesized a significant relationship between agility and scoring accuracy in the subjects understudy. The subjects were 20 players from soccer schools in Baghdad. The tests were selected and applied from 1/2/2018 – 6/3/2018. The data was collected and treated using proper statistical operations. The researcher concluded that youth players have high level of agility and it is related to accuracy. Finally، he recommended the necessity of developing agility due to its great effect on developing scoring as well as making similar studies on the effect of each motor and physical ability on the other skills.